Biomassa para fins energéticos em uma indústria de painéis de madeira - Hansted, Ana Larissa Santiago (2017)
The bark is a residue that can be used as fuel by industry. One of the problems of the use is the contamination. The purpose of this paper was the physico-chemical characterization of eucalyptus bark used as a fuel in a wood panel industry, relating the high heating value (HHV) with the ash content. Six treatments were provided according to the particle size: T1 (850µm to 425 µm / unwashed), T2 (250 µm / unwashed), T 3 (<150 µm / unwashed), T4 (850µm to 425 µm / washed), T5 (250 µm / washed), T6 (<150 µm / washed). The material was assessed regarding moisture content. The treatments were subjected to HHV and proximate analysis. The ashes were analyzed under SEM - EDS in order to identify the components/contaminants. The data obtained in this study were statistically analyzed using the software R. The material presented moisture content of 70% on a dry basis, which is considered high for use in bioenergy. Contaminants comp onents such as calcium and silica were identified in the ash material. The proximate analysis showed a significant difference among treatments, the ash content presented values from 2.63% (T1) to 13.86% (T3). The process of washing the bark was efficient f or the reduction in ash content only in the particle size <150 µm. The separation in particle size extracts of the bark presented a good technique to reduce the contaminants.